Purchase Intention on Low-Cost Smartphone in Terms of Well Established Smartphone Brand Users - Putri, Radha Shafira; Suarly, Theresia Christania; Alaric, William; Manaf, Peri Akbar (Emerging Markets : Business and Management Studies Journal, 2021)
This study investigates the effects of brand image on customer trust and perceived value, as well as its influence on the purchase intention of Realme smartphones in Indonesia. The model for this study indicates the effects of brand image on purchase intention, which is mediated by customer trust and customer perceived value. The data sample was collected from 265 respondents using non-probability sampling techniques with the purposive sampling method through online surveys. The use of PLS-SEM methodology by SmartPLS analyzed the result showing the significance of customer trust and customer perceived value on affecting purchase intention, whereby brand image has a significant and positive impact on customer trust and customer perceived value in Realme smartphones, from the high-cost smartphone brand users perspectives. Based on prior research, we apply a theory from a new angle by examining brand image influence on consumer trust and customer perceived value, as well as its impact on purchase intention in Realme smartphones as observed by users of well-known smartphone brands. Keywords: Brand Image, Customer Trust, Customer Perceived Value, Purchase Intention, Smartphone.